The Analysis of Statement of Cash Flow in Assessing the Financial Performance at PT Akasha Wira International TBK: Analisis Laporan Arus Kas dalam Menilai Kinerja Keuangan Pada PT Akasha Wira International TBK - Adi Harianto; Ester; Zulkheiri (Jurnal Kolaboratif Sains, 2023)
The statement of cash flow has an important role in helping to assess the financial performance of a company. Cash flow information assists its financial statement users in obtaining the relevant information concerning the source and use of virtually the entire financial system over a given period of time. Cash flow is a concept in accounting and finance used to describe the inflow represent cash receipts while outflow relate to cash expenditure. Cash flow of a company is a crucial factor that enhances its operations. Due to the relevance of cash flows in the company’s operations and performance, companies need to develop a suitable cash flow and apply it in order to maximize shareholders values. Cash flow can be used as effective way of forecasting the company’s ability in providing profit in future. If the company has lack of cash, the company will have difficulties in conducting the business activities such as making purchasing, making investment and paying the loan. The purpose of this research is to know result of analysis of cash flow in determining the financial performance at PT Akasha Wira International, Tbk. Research design used in this research is descriptive research design with conducting financial statement analysis. Research methods which used are descriptive statistic analysis with financial ratio analysis. The conclusion of this research is that financial performance in PT Akasha Wira International Tbk isn’t good based on analysis of cash flow. There is decreasing of cash flow in year 2012-2016. It shows that there is decreasing of company’s ability in paying liabilities and generating income with using cash. The company doesn’t manage the cash flow properly with result that the company will have lack of cash in developing the business. There is increasing of liabilities in conducting business activities. The company cannot collect the account receivable quickly. The cash isn’t used properly in generating sales. There is decreasing of financial performance in year 2012-2016. It shows that there is decreasing of the company’s ability in generating income. The company cannot increase the sales significantly because there is change of customer demand and choice. The company doesn’t make innovation in developing the new product with considering the customer’s expectation.